SOX10-positive cells emerge in the rat pituitary gland during late embryogenesis and start to express S100β - Ueharu, Hiroki; Yoshida, Saishu; Kanno, Naoko; Horiguchi, Kotaro; Nishimura, Naoto; Kato, Takako; Kato, Yukio (Cell and tissue research, 2018)
In the pituitary gland, S100β-positive cells localize in the neurohypophysis and adenohypophysis but the lineage of the two groups remains obscure. S100β is often observed in many neural crest-derived cell types. Therefore, in this study, we investigate the origin of pituitary S100β-positive cells by immunohistochemistry for SOX10, a potent neural crest cell marker, using S100β-green fluorescence protein-transgenic rats. On embryonic day 21.5, a SOX10-positive cell population, which was also positive for the stem/progenitor cell marker SOX2, emerged in the pituitary stalk and posterior lobe and subsequently expanded to create a rostral-caudal gradient on postnatal day 3 (P3). Thereafter, SOX10-positive cells appeared in the intermediate lobe by P15, localizing to the boundary facing the posterior lobe, the gap between the lobule structures and the marginal cell layer, a pituitary stem/progenitor cell niche. Subsequently, there was an increase in SOX10/S100β double-positive cells; some of these cells in the gap between the lobule structures showed extended cytoplasm containing F-actin, indicating a feature of migration activity. The proportion of SOX10-positive cells in the postnatal anterior lobe was lower than 0.025% but about half of them co-localized with the pituitary-specific progenitor cell marker PROP1. Collectively, the present study identified that one of the lineages of S100β-positive cells is a SOX10-positive one and that SOX10-positive cells express pituitary stem/progenitor cell marker genes.